To what extent does the EU usefully promote economic and social rights through human rights clauses in its trade agreements? - Han, Ji Sun (2024)
This thesis evaluates the extent to which the EU usefully promotes economic and social rights (ESR) through human rights clauses (HRC) in its trade agreements. HRC establish respect for human rights as an essential element of the parties’ agreements and enable the parties to take appropriate measures in response to breaches of their obligations under HRC. HRC further provide a legal reference point for the parties’ positive measures which promote ESR within the framework of trade agreements. Given that ESR tend to be given less priority than civil and political rights (CPR) in the international community, and given that EU trade agreements have developed in a manner which has strengthened the link between trade and ESR, it is necessary to examine whether the EU is making use of the opportunities provided by HRC in its trade agreements to usefully promote ESR. Two case studies have been undertaken for this purpose, in order to analyse the measures taken by the EU to promote ESR through HRC in practice. The first case study focuses on the EU’s trade agreement with Korea, and the second case study focuses on the EU’s trade agreement with Colombia and Peru.